Aristotle's Problemata in Different Times and Tongues - Goyens, Michele; De Leemans, Pieter (Book collections on Project MUSE., 2006)
The present volume contains a collection of papers on the reception of Aristotle''s Problemata, a multifaceted text asking various questions about medical, scientific or everyday topics. This text is one of the most neglected Aristotelian treatises, because of its heterogeneous character and its so-called ''inauthenticity''. It has been the subject of a complex transmission. In ancient times, Aristotle''s text has been augmented and adapted, while still other authors composed similar collections of Problemata. In the Middle Ages, Problemata collections have been translated into Arabic, Latin,